2022
DOI: 10.1109/tvcg.2021.3114823
|View full text |Cite
|
Sign up to set email alerts
|

Visual Arrangements of Bar Charts Influence Comparisons in Viewer Takeaways

Abstract: Well-designed data visualizations can lead to more powerful and intuitive processing by a viewer. To help a viewer intuitively compare values to quickly generate key takeaways, visualization designers can manipulate how data values are arranged in a chart to afford particular comparisons. Using simple bar charts as a case study, we empirically tested the comparison affordances of four common arrangements: vertically juxtaposed, horizontally juxtaposed, overlaid, and stacked. We asked participants to type out w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 63 publications
3
12
0
Order By: Relevance
“…Additionally, we controlled for the type of visualization used by asking participants to read similar line charts with overlaid scattered dots. These design choices limit our ability to generalize our findings to other visualization types, as visualization techniques can profoundly impact human perception and decision-making [93,94,96]. Furthermore, we did not vary the number of data points in the current experiments and only asked participants to synthesize two pieces of information.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Additionally, we controlled for the type of visualization used by asking participants to read similar line charts with overlaid scattered dots. These design choices limit our ability to generalize our findings to other visualization types, as visualization techniques can profoundly impact human perception and decision-making [93,94,96]. Furthermore, we did not vary the number of data points in the current experiments and only asked participants to synthesize two pieces of information.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Cardinality: Comparison utterances can express relationships between individual entities, e.g., "compare the effectiveness of treatment A to treatment B", as well as relationships between individuals and larger sets containing multiple entities, e.g., "compare the effectiveness across all treatments". Similar to the process described by Xiong et al [69], we list four cardinalities for the entities in comparison utterances in the context of visual analysis:…”
Section: Design Space Of Comparison Utterancesmentioning
confidence: 99%
“…2. Examples of two sets of spatial arrangements for visual comparisons based on findings from Xiong et al [69]. Results found that stacking small multiples vertically tends to elicit 1-to-1 comparisons of individual values in a set, whereas aligning them horizontally tends to elicit a comparison of the two sets as two groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations